2015
DOI: 10.1038/srep15248
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium-Infected Dendritic Cells Disseminate Granulomatous Inflammation

Abstract: The disappearance and reformation of granulomas during tuberculosis has been described using PET/CT/X-ray in both human clinical settings and animal models, but the mechanisms of granuloma reformation during active disease remains unclear. Granulomas can recruit inflammatory dendritic cells (iDCs) that can regulate local T-cell responses and can carry bacteria into the lymph nodes, which is crucial for generating systemic T-cell responses against mycobacteria. Here, we report that a subset of mycobacterium-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 48 publications
2
31
0
Order By: Relevance
“…These inflammatory effector cells have a limited lifespan, and so continuous cell replacement and granuloma reformation is needed to maintain granulomas long-term. (Harding et al, 2015b). In fact, more than a third of monocytes are replaced within in a week in a granuloma transplantation model, and dendritic cells and (Schreiber et al, 2011b) and lymphocytes (Schreiber et al, 2011a) have a similar turnover rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These inflammatory effector cells have a limited lifespan, and so continuous cell replacement and granuloma reformation is needed to maintain granulomas long-term. (Harding et al, 2015b). In fact, more than a third of monocytes are replaced within in a week in a granuloma transplantation model, and dendritic cells and (Schreiber et al, 2011b) and lymphocytes (Schreiber et al, 2011a) have a similar turnover rate.…”
Section: Discussionmentioning
confidence: 99%
“…Granuloma transplantation was performed as previously described (Harding et al, 2015b;Schreiber et al, 2011b). Mice were anesthetized with a ketamine/xylazine mixture and given meloxicam subcutaneously for post-operative pain management.…”
Section: Methods Details Granuloma Transplantationmentioning
confidence: 99%
“…Additionally, the mycobacterial serine hydrolase Hip1 reduced surface expression of MHC class II and the costimulatory molecules CD40 and CD86, as well as a number of pro‐inflammatory cytokines . Several groups have also reported that infection of DCs with M. tuberculosis reduces their expression integrins and chemokine receptors, therefore hindering their migration to lymph nodes and delaying the onset of adaptive immunity . It is also thought that the cross‐presentation of M. tuberculosis antigens is prevented by the inhibition of apoptosis of infected phagocytes, as discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…Previous data from our group showed that after in vivo BCG infection, primary granulomas are formed from where immune cells carrying live bacteria exit. These cells were identified as CD11c+ DCs (Harding et al, 2015), which arrest with CD4+ T cells in the body at different distances from the primary focus, forming new secondary granulomas and promoting dissemination. Concurrently, the migratory capacity of infected cells isolated from liver granulomas were studied and revealed that phagocytic cells carrying mycobacteria are hindered in motion (Harding et al, 2015).…”
Section: Commentary Background Informationmentioning
confidence: 99%
“…Mycobacterium tuberculosis (Mtb) primarily infects the lung, resulting in pulmonary granuloma formation, but disseminating bacteria can spread to the central nervous system (CNS) and form lesions in the parenchyma, causing serious neurological symptoms and high mortality (Jain et al, 2018). Previous studies from our laboratory have shown that dendritic cells (DCs) in vivo are capable of escaping primary granulomas and contribute to Mtb dissemination (Harding, Rayasam, Schreiber, Fabry, & Sandor, 2015); however, the mechanism by which Mtb then enters the CNS is not yet clear. The model presented here allows us to test different mechanisms, including the "Trojan horse" theory, which favors Mtb dissemination into the CNS via cellular transport.…”
Section: Introductionmentioning
confidence: 99%